Combination of a peptide-modified gellan gum hydrogel with cell therapy in a lumbar spinal cord injury animal model - Gomes, Eduardo D. (2016)
Spinal Cord Injury (SCI) is a highly incapacitating condition for which there is still no cure. Current clinical approaches are mainly based on palliative care, so there is a need to find possible treatments to SCI. Cellular transplantation is regarded with great expectation due to the therapeutic potential of cells such as Adipose tissue-derived Stromal/Stem Cells (ASCs) or Olfactory Ensheathing Cells (OECs). Both are accessible sources and present positive paracrine and cell-to-cell interactions, previously reported by our group. Additionally, biomaterials such as hydrogels have been applied in SCI repair with promising results. We propose to combine a GRGDS-modified gellan gum hydrogel with ASCs and OECs in order to promote SCI regeneration. In vitro, ASCs and OECs could be co-cultured within GG-GRGDS hydrogels inducing a more robust neurite outgrowth when compared to controls. In vivo experiments in a hemisection SCI rat model revealed that the administration of ASCs and OECs encapsulated in a GG-GRGDS hydrogel led to significant motor improvements when compared to both control (SCI) and hydrogel alone (GG-GRGDS) groups. This was accompanied by a decreased infiltration of inflammatory cells and astrocytes, and by an increased intensity of neurofilament. These results suggest evident gains induced by the encapsulation of ASCs and OECs in GG-GRGDS based hydrogels.